De Novo Vogt-Koyanagi-Harada Disease following Covid-19 Vaccine: A Case Report and Literature Overview. (4th July 2022) - Brunet de Courssou, Jean-Baptiste; Tisseyre, Mylène; Hadjadj, Jérôme; Chouchana, Laurent; Broca, Florent; Terrier, Benjamin; Duraffour, Pierre; Henriquez, Soledad
ABSTRACT: Purpose: To describe a case of Vogt-Koyanagi-Harada (VKH) disease after a Covid-19 mRNA vaccine (tozinameran) and to present the results of a pharmacovigilance disproportionality study. Methods: A retrospective chart review and a pharmacovigilance disproportionality study using the WHO global individual case safety reports database (VigiBase). Results: A 57-year-old female with no medical history developed a VKH disease 3 weeks after Covid-19 mRNA vaccine. Symptoms at onset were headaches and blurred vision associated with aseptic meningitis and bilateral diffuse granulomatous panuveitis with serous retinal detachment. One month from diagnosis and glucocorticoids treatment, the patient recovered. Five similar cases have been reported in VigiBase. VKH disease is disproportionately reported with tozinameran and other vaccines. Conclusion: VKH disease is disproportionately reported with tozinameran, suggesting a possible safety signal. Cases after vaccination support the screening for any possible immune triggers such as vaccines when assessing patients with VKH disease.